Distributive Justice for Volunteers: Extrinsic Outcomes Matter. Issue 3 (5th December 2016) - Hurst, Christine; Scherer, Lisa; Allen, Joseph
Abstract : Volunteer organizations continue to suffer from turnover; the current volunteer rate is the lowest since 2002. Distributive justice, satisfaction, and extrinsic outcome importance were examined as influences of volunteer intention to quit. Survey results from 294 volunteers revealed that those who perceived less than fair distribution of extrinsic outcomes experienced heightened intention to quit compared to those who perceived fair distribution. Overall satisfaction partially mediated this relationship. We explored the potential moderating role of volunteers' assessment of the importance of extrinsic outcomes on the overall mediated relationship.